2009
DOI: 10.1007/s11418-009-0367-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of anti-inflammatory and antioxidant activities of Peltigera rufescens lichen species in acute and chronic inflammation models

Abstract: The anti-inflammatory effects of the methanol extract of the lichen species Peltigera rufescens (Weis.) Humb (MEPR) (Peltigeraceae) on acute (carrageenan-induced) and chronic (cotton pellet granule) phases of inflammation were investigated. The MEPR was capable of reducing carrageenan-induced inflammation and showed a potent antiproliferative effect (63.5%) in the chronic inflammation model. Inflammation is related to neutrophil infiltration and the production of neutrophil-derived mediators and free radicals.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
50
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 36 publications
3
50
1
Order By: Relevance
“…Sitagliptin medication decreased serum levels of total cholesterol and triglyceride (Qin et al, 2005;Monamie et al, 2012;Picatoste et al, 2013). A decrease in postprandial triglycerides with sitagliptin therapy was also reported by (Tremblay et al, 2011;Kubota et al, 2012). Multiple action mechanisms are assumed for the triglyceride-lowering effect of sitagliptin, including inhibited TAG absorption from the intestines, inhibited VLDL-c release from the liver, and decreased blood glucose levels and accompanying improvements in metabolic status (Monami et al, 2011;Cobble and Frederich, 2012).…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Sitagliptin medication decreased serum levels of total cholesterol and triglyceride (Qin et al, 2005;Monamie et al, 2012;Picatoste et al, 2013). A decrease in postprandial triglycerides with sitagliptin therapy was also reported by (Tremblay et al, 2011;Kubota et al, 2012). Multiple action mechanisms are assumed for the triglyceride-lowering effect of sitagliptin, including inhibited TAG absorption from the intestines, inhibited VLDL-c release from the liver, and decreased blood glucose levels and accompanying improvements in metabolic status (Monami et al, 2011;Cobble and Frederich, 2012).…”
Section: Discussionmentioning
confidence: 79%
“…Elevation in mRNA expression of acyl CoA synthease and Carnitinepalmitoyltranferease and depression in hepatic acyl CoA transferase mRNA expression in the liver could be the possible mechanism of hypolipdemic effect of L-carnitine (Mun et al, 2007). Sitagliptin significantly lowered the circulating cholesterol, triglycerides and LDL-cholesterol, with a significant increase in the HDL-cholesterol in diabetic rats (Tremblay et al, 2011;Saker, 2013) as well as in uncontrolled diabetes (Chawla et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, lichens were used as raw materials in paint and cosmetic industry, as environmental indicators, as food and as medicine for various purposes (Cocchietto et al 2002;Dilsizoglu et al 2004;Yazıcı and Aslan 2006;Svoboda 2007). The anti-inflammatory effect of methanol extract of the lichen species Peltigera rufescens was reported for its reducing effect on the neutrophil-derived free radicals and its ameliorating effect on the anti-oxidant defense systems (Tanas et al 2010). Likewise, Halici et al (2005) reported that, the water extract of the lichen, Usnea longissima, has protective effect in indomethacin-induced ulcers, which can be attributed to its anti-oxidant potential.…”
Section: Introductionmentioning
confidence: 99%
“…Peroxidation is a phenomenon that can alter the functionality of the membranes (rich in polyunsaturated fatty acids) by altering their permeability and fluidity etc. Model of inflammation induced by carrageenan used in the study by some authors accompanied to increased production of peroxidized lipids (Tanas et al, 2010). And also lipid peroxidation was reported as complicating the inflammatory process (Uzkeser et al, 2012).…”
Section: Discussionmentioning
confidence: 99%